Em defesa do contextualismo moderado: por uma semântica sensível para adjetivos comparativos. - Barbosa, Eduarda Calado (2011)
In this work, we offer a general presentation of the debate in philosophy of language between Contextualism andMinimalism. We also offer a defense of a contextualist account of the meaning of comparative adjectives, through a refutation of the objections present in H. Cappelen and E. Lepore s book, Insensitive Semantics.